(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The adolescent’s right to participate in decisions concerning his or her health represents, on closer inspection, a subsystem of the general model of consent to treatment, which takes into account the need for clinical approaches designed on the person, respectful of his or her wishes and inclinations.